Cell-Free Scaffolds in Cartilage Knee Surgery: A Systematic Review and Meta-Analysis of Clinical Evidence. (July 2021) - Andriolo, Luca; Reale, Davide; Di Martino, Alessandro; Boffa, Angelo; Zaffagnini, Stefano; Filardo, Giuseppe
Objective: To evaluate current evidence and results of cell-free scaffold techniques for knee chondral lesions. Design: A systematic review was conducted on 3 medical electronic databases according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) guidelines, and the methodological quality was assessed with a modified Coleman Methodology Score. A meta-analysis was performed on the articles reporting results for visual analogue scale (VAS), Lysholm, and International Knee Documentation Committee (IKDC) scores. In order to investigate the clinical results improvement over time of cell-free cartilage scaffold implantation, all scores were reported and analyzed as improvement from basal scores at 1, 2, and ≥3 years' follow-up. Results: A total of 23 studies involving 521 patients were included in the qualitative data synthesis. The Coleman score showed an overall poor study quality with the majority of studies reporting results at short-/mid-term follow-up. Sixteen studies were included in the meta-analysis, showing a significant improvement from basal score at 1, 2, and ≥3 years' follow-up. The improvement reached at 1 year remained stable up to the last follow-up for all scores. Conclusions: The current literature suggests that cell-free scaffolds may provide good clinical short-/mid-term results; however, the low evidence of the published studies and their short mean follow-up demand further evidence before more definitive conclusions can be drawn on their real potential over time and on their advantages and disadvantages compared to the cell-based strategies for the treatment of cartilage lesions.